Determinants of Quality of Life among Patient with Knee Osteoarthritis - Wika Yuniarwati; Achmad Arman Subijanto; Hanung Prasetyo (Masters Program in Public Health, 2019)
Background: Osteoarthritis (OA) ranks second after cardiovascular disease as the cause of physical disability. Nearly 25% of individuals aged 55 years or over have complaints of knee pain and some have proven osteoarthritis. Elderly people with OA suffer from depression, reduced quality of life and economic difficulties. In assessing the quality of life of OA patients can help identify the health care needs of all patients. This study aimed to determine factors affecting quality of life in knee OA patients.Subjects and Method: This was analytic observational study with a cross sectional design. The study was carried out at Dr. Moewardi and UNS Hospital, Surakarta, Central Java. A sample of 180 OA knee patients was selected by consecutive sampling. The dependent variable was quality of life. The independent variables were sex, occupation, body mass index, duration of illness, and pain location. The data were collected by questionnaire and analyzed by a multiple logistic regression.Results: Quality of life of OA knee patient decreased with female (b= -1.11; 95% CI= -2.32 to 0.08; p= 0.069), overweight/ obesity (b= -1.64; 95% CI= -2.35 to -0.93; p<0.001), duration of chronic illness (b= -0.80; 95% CI= -1.51 to -0.91; p= 0.027), and bilateral pain (b= -0.74; 95% CI= -1.42 to -0.05; p= 0.034).Conclusion: Quality of life of OA knee patient decreases with female, overweight/ obesity, duration of chronic illness, and bilateral pain.Keywords: quality of life, kne eosteoarthritis, logistic regressionCorrespondence: